Assessment of mechanical properties, microstructure and fracture mechanism of SA-508 Gr.3 Cl.1/SS 316L bimetallic joint. (22nd May 2021) - Rahim, Tahir; Anjum, Muhammad Ammar; Zeb, Jahan; Mohsin, Amena; Farooq, Muhammad; Jan, Miraj M.; Ahmad, Zaheer
Bimetallic joints of carbon steel SA-508 Gr.3 Cl.1 and stainless steel SS-316L are extensively used in nuclear power plants (NPPs) and petrochemical industry. Severe service conditions during the operation of an NPP involving high temperature, pressure and corrosion rates; make these weldments of extreme importance. The objective behind the present study is to explore the weld quality and mechanical properties of these bimetallic joints prepared by shielded metal arc welding process, using inconel electrode. The prepared bimetallic joint showed improved strength and toughness as compared to the base metals. Fractography results obtained from stereomicroscopy and scanning electron microscopy proved that fracture was ductile due to coalescence of micro voids. X-Ray diffraction and X-Ray energy dispersive spectroscopy results showed the absence of second phase in the joint. The obtained fracture toughness of weld though acceptable is lesser than base metals.